Characterization of immiscible phase displacement in heterogeneous pore structures: Parallel multicomponent lattice Boltzmann simulation and experimental validation using three-dimensional printing technology - Ju, Yang; Gong, Wenbo; Zheng, Jiangtao (International journal of multiphase flow, 2019)
•Immiscible oil-water displacement in heterogeneous pore structures is investigated.•A multicomponent lattice Boltzmann model with high-resolution meshes is proposed.•A realistic pore model is built using three-dimensional printing (3DP) technology.•The simulation is validated by the experimental data.•The effect of interface distributions on the displacement is characterized. Understanding and characterization of immiscible-fluid displacement mechanisms in pore structures are required for enhanced hydrocarbon resource recovery in unconventional tight reservoirs. The displacement process of immiscible fluids in a porous structure on the pore scale has been widely simulated and characterized via lattice Boltzmann (LB) methods. However, owing to the heterogeneity and tortuosity of rock pore structures, it is difficult to numerically represent the real irregular geometry and accurately describe the varied immiscible interfaces in experiments using LB simulation. A low mesh resolution is usually applied, which causes simulation inaccuracy compared to realistic displacement behaviors. In this study, we introduce a multicomponent LB model with high-resolution meshes to investigate immiscible oil-water displacement in heterogeneous pore structures. The pore-scale LB model is established using information extracted from a realistic reservoir rock. A parallel computing algorithm is integrated into the model to accelerate the LB simulation. To verify the LB simulation, an oil-water displacement experiment is conducted using a transparent pore model replicated using three-dimensional printing (3DP) technology and information on the real porous rock. Owing to the sensitivity of the interfacial condition at the inlet, the inlet buffer was designed to relieve injecting perturbations in experiments, and an artificial velocity profile was applied in the simulation to approximate this relieved interface. Comparison of the LB simulation and experiment data indicates that the suggested parallel multicomponent LB method can simulate the oil-water displacement process in heterogeneous pore structures well. This study provides a method for characterizing the immiscible fluid displacement mechanism in a porous structure and forecasting the preferential flow path in a heterogeneous structure with a certain water wettability.